2002
DOI: 10.4049/jimmunol.169.2.722
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD4 T Cell Changes in Murine AIDS Is Dependent on Costimulation and Involves a Dysregulation of Homeostasis

Abstract: Strong CD4 T cell activation and proliferation are seen in susceptible mice infected with the murine retroviral inoculum, LP-BM5, which produces an immunodeficiency syndrome called murine AIDS (MAIDS). We developed a short term adoptive transfer model of MAIDS to examine the requirements for the CD4 T cell response. Naive CD4 T cells from uninfected donors responded quickly after adoptive transfer into MAIDS-infected hosts, becoming activated and proliferating within several days. Using blocking mAbs to costim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The LP-BM5 retrovirus mixture was administered intraperitoneally to mice in 0.1 ml of minimum essential medium with an esotropic titer of 4.5 log 10 plaque-forming units ϫ 10 Ϫ3 /l, which induces TH2 dominant lymphocyte function comparable with that previously published (17,20,47,58). The mice were infected with LP-BM5 2 wk before treatment with the TCR-V␤ peptides, as done previously in earlier studies (27,40,49).…”
Section: Lp-bm5 Viral Infectionmentioning
confidence: 97%
See 1 more Smart Citation
“…The LP-BM5 retrovirus mixture was administered intraperitoneally to mice in 0.1 ml of minimum essential medium with an esotropic titer of 4.5 log 10 plaque-forming units ϫ 10 Ϫ3 /l, which induces TH2 dominant lymphocyte function comparable with that previously published (17,20,47,58). The mice were infected with LP-BM5 2 wk before treatment with the TCR-V␤ peptides, as done previously in earlier studies (27,40,49).…”
Section: Lp-bm5 Viral Infectionmentioning
confidence: 97%
“…We found no significant increase of LP-BM5 copy numbers as detected by cPCR over time (data not shown). LP-BM5-induced TH2 lymphocyte function is rapid and sustained until the death of the mouse (17,20,28,47,58). We have reported that ventricular dilation and decreased ␤ occurs in the absence of cardiac lymphocytic infiltrates and inflammatory mediators (4,40).…”
Section: H647mentioning
confidence: 98%
“…Several studies have examined the effects of established MAIDS disease on the CD4 T-cell compartment, i.e., characterization of CD4 T-cell anergy (2,21,41,59), but there are few prospective studies defining the role of these CD4 T-cell features in the induction of MAIDS. The molecular basis for the requirement for CD4 T cells for MAIDS induction is thus incompletely understood.…”
mentioning
confidence: 99%